Covid-19 Impact on The Marine Community Economy (Study of Sales at Mopah Market) - Kaok, Maria (Universitas Airlangga, 2021)
This paper aims to analyze the Impact of Covid-19 on the Marine Community's Economic (Study of Sales at Mopah Market). The population in this study was 33 respondents, using a saturated sample technique. This writing uses a quantitative approach with simple regression analysis techniques using SPSS 22. The results obtained are that there is a positive and significant influence on the Marine community's economy. Judging from the effects of data analysis, it shows that during the Covid-19 pandemic, the organization experienced a decrease in income. It is indicated by the results of the value of t-count = 5.068 and t-table = 1.695, sig = 0.000. From the result, we know that there is an impact of Covid-19 on the Marine people's economy in their sales in the Merauke regency Mopah market. The total revenue for sales before Covid-19 was 56% and 44% after Covid-19 was a negative impact that affected the Marine community's economy by a difference of 12%. This difference shows that Covid-19 has an impact on the economy in terms of income from daily sales. This impact caused the community to experience a decrease in their income during the Covid-19 pandemic. Keywords: Covid-19, Community Economy JEL Classifications: C10, Q0, A10